Bahasa Inggris - Misbahuddin Asaad; Maharida; Abdul Rauf, Rusmin (Universitas Islam Negeri Alauddin, 2025)
This paper intends to shed light on a crucial stage in hadith research, between the sanad and the matan, which took place in the mid-19th century CE, when the figure of Salah al-Din Idlibi offered a new formula of matan criticism, and was considered strange and unnecessary, especially when it was presented by a lesser-known person, who could perhaps be compared to the big names, with the findings of the sanad research method. Ignaz Goldziher for example (1850-1921), who inspired many orientalists, like Jonathan A. C Brown. Writing using the qualitative-narrative-inductive writing method, with a socio-historical approach, finds that, criticism of matn becomes an anti-climax of procedural hadith research with scientific bids or hadith scientific methodology, which makes hadith a multilateral function in reading contemporary issues that covered by advances in technology and science. It was found that the sanad as a narrator ending with the editor of the hadith text/matn, must consciously ensure that the utterance was transmitted from the Prophet, with the correct events, according to the rules of the language, according to the social situation when each narrator in the Isnād chain intersects without disconnected based on the historical elements of each sanad.